The Impact of Entrepreneurship, R&D Internal Capabilities and R&D External Collaboration on Innovation Performance in MAPNA Industrial Group - Abbas Khamseh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Many factors affect the firm's innovation performance, and identifying these factors can help managers better plan and manage the innovation process. MAPNA Industrial Group, as a manufacturer of power plant products, seeks to improve and enhance its subsidiaries' innovation performance to gain a competitive advantage and presence in global markets. Accordingly, the present study investigated the impact of entrepreneurship, R&D internal capabilities, and R&D external collaboration on MAPNA's innovation performance.Methodology: This study is a descriptive and applied research. Data collection was done using library and field study methods. A questionnaire and interview were used to benefit from experts' opinions, including 30 managers and experts in the R&D departments of MAPNA Group. Fourteen indicators in the form of three factors of entrepreneurship, R&D internal capabilities, and R&D external collaboration, were identified. Then conceptual research model was designed, and innovation performance was evaluated using a fuzzy approach and MATLAB software.Findings: The results show that all three factors of R&D internal capabilities, R&D external, and entrepreneurship collaborations have a direct and positive effect on MAPNA Group's innovation performance, and R&D internal capabilities have the most impact, with a score of 7.44. Entrepreneurship has the least impact, with a score of 5.64. Also, innovation performance has the most impact, respectively, on the indicators of the investment in R&D software, the amount of investment in equipment and laboratories, and the percentage of R&D costs of the organization's total sales. All three are indicators of R&D internal capabilities. The level of innovation performance in the MAPNA group was 6.44, which is in the medium to high range.Originality/Value: This study proposed a conceptual model to illustrate the relationship between intrapreneurship, R&D internal capabilities, and R&D external collaboration to engender innovative performance of MAPNA.